(untitled) (Laisvalaikio tyrimai, 2024)
Research background. In the 21st century, ever-improving technologies and the related improvement of other services have encouraged the modernisation of the processes of all organisations. Museums are no exception (Šimanskienė, Valiušienė, Sloka, 2017). This rapid jump over the past year has been fuelled by the onset and rapid acceleration of the COVID-19 pandemic, which has resulted in numerous bans and restrictions. The pandemic has forced humanity to broaden its horizons or even change its interests. The museums started making virtual tours of exhibitions, video stories about works and expositions, or creating newsletters that packed virtual art games, discoveries, and gifts. To attract as many visitors as possible, museums have likewise attempted to improve their inventory but also to implemented never-before-seen virtual reality plans or projects while maintaining the originality characteristic of culture. The tourism sector was particularly affected, as the activities of travel or cultural organisations and companies were restricted or suspended. Only a part of organisations or companies carried out their activities remotely. The research problem. During the pandemic, Lithuanian museums were not ready to present themselves in a digital format, but quickly reoriented themselves. They started making virtual tours showing exhibitions, video stories about works and expositions, or creating newsletters that packed virtual art games, discoveries, and gifts (Tomkevičiūtė, 2020). To attract as many visitors as possible, museums have likewise attempted to improve their inventory but also to implemented never-before-seen virtual reality plans or projects while maintaining the originality characteristic of culture. The offer of museum services still lacks integrated virtual services that would improve the museum’s expositions and increase the number of visitors, so it is essential to find out why the integration of these services is not being expanded so rapidly. The aim of the study is to analyse the integration of virtual reality in the museums of Lithuania. The subject of study is the integration of virtual reality in museums. Methods. To reveal the object of the research - the application of virtual reality in museums, the research was carried out in several stages, choosing research methods such as scientific literature analysis, semi-structured interviews for data collection, and qualitative content for data analysis. Taking into account the selected research strategy, the selection of subjects was guided by the provision that all 5 specialists/experts working directly with service VR “Angelų takais” in the National M.K. Čiurlionis museum departments in Kaunas and Druskininkai will be interviewed. The interview questionnaire consisted of categories: preparation, service evaluation, service impact, and satisfaction. The questions are based on Gutowski and Klos-Adamkiewicz (2020) assessment model. The model consisted of virtual reality content, navigation, interactivity, functionality, additional options, graphics, accessibility for all groups, intuitiveness, multi-language capabilities. The collected data were transcribed and analysed using qualitative content analysis. Results and conclusions. The application of virtual reality has been a major impact on the revival of the cultural sector affected by the pandemic and has given a second life to museums. According to the experts, there was also a great impact on society - those who were not interested in art began to be interested in it in the virtual reality form. The qualitative research showed the possibilities of applying this kind of virtual tour service “Angelų takais” to other offerings at the M.K. Čiurlionis National Museum of Art. Till now this tour doesn’t have an educational function, but it will be integrated soon, the shortcomings and advantages of the service were noted, and the peculiarities were described. The success of this service was influenced by the reputation of the artist himself, whose paintings the museum is named after. Keywords: virtual reality, virtual tour, VR museum, VR service.